Tongues of fire: An interpretation of mexican independence as counter-revolution (1821-1823) - Rosa, Josep Escrig (Revista do Instituto Histórico e Geográfico Brasileiro, 2023)
The article proposes an interpretation of the independence of Mexico and the First Empire between 1821 and 1823 from the perspective of counter-revolution and anti-liberalism. Sermons and manuscripts are analyzed to present the various arguments put forth by certain conservative ecclesiastics. They adapted their discourse to challenge the Spanish revolution of 1820, and denounced that the Cortes were adopting measures that attacked the throne and the altar. These religious figures believed that independence would safeguard Mexico from the influence of Hispanic liberalism, although they were mistaken. Nonetheless, during the years specified above they struggled to reverse the revolutionary process and control the political situation.